2012
DOI: 10.4236/ojms.2012.24021
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Phylogenetic Analysis of Deep-Sea Bacteria Capable of Metabolizing Lignin-Derived Aromatic Compounds

Abstract: Lignin is one of the most abundant biomasses in nature. It is composed of aromatic moieties and has great potential for use in the production of chemical alternatives to petroleum products. Because of increasing interest in biocatalysis, the potential for industrial application of microbial metabolism of lignin-derived compounds has gained considerable recent attention. Functional screenings of culturable bacteria isolated from sediments and sunken wood collected from the deep sea revealed the existence of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…We previously isolated several deep-sea bacteria capable of metabolizing lignin-derived aromatic monomers 27 . Here, we screened the isolates for strains capable of cleaving the β -O- 4 ether linkage of the dimeric lignin model compound GGGE ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously isolated several deep-sea bacteria capable of metabolizing lignin-derived aromatic monomers 27 . Here, we screened the isolates for strains capable of cleaving the β -O- 4 ether linkage of the dimeric lignin model compound GGGE ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To gain deeper insight into the involvment of microbes to lignin degradation in marine environments, we previously conducted functional screening of microbes isolated from deep-sea sediments and highly decomposed submerged wood, and identified a number of bacterial strains capable of degrading lignin-derived aromatic monomeric compounds 27 . Here, we screened this collection of marine isolates for microbes with β -O- 4 ether linkage cleavage activity and mined the genes required for the reaction from the genomic sequence 28 of one identified strain.…”
mentioning
confidence: 99%
“…Several actinomycetes strains such as Streptomyces setonii, Rhodococcus opacus, and Corynebacterium glutamicum have this mechanism and catabolize HBA as well as other lignin derivatives (45)(46)(47)(48)(49). Microbacterium lacus isolated from deep-sea sediments can metabolize HBA (50), although, to the best of our knowledge, a Microbacterium mechanism for metabolizing HBA has not been reported. Database searches revealed that some Microbacterium strains possess a complete set of genes for the ␤-ketoadipate pathway (data not shown), indicating that Microbacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of microbial pathways for using a wide variety of aromatic molecules as carbon sources was likely triggered by naturally produced aromatic compounds during lignin decomposition by some microorganisms ( 5 ). We recently isolated a marine Novosphingobium strain, isolated from sunken wood recovered from a depth of 260 m in Suruga Bay, off the Pacific coast of Shizuoka Prefecture, central Japan ( 6 ). The strain was found to metabolize a wide range of lignin-related aromatic monomers.…”
Section: Genome Announcementmentioning
confidence: 99%